2015
DOI: 10.4038/ijptsud.v1i3-4.7837
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of HIV, Hepatitis B and Hepatitis C testing among injection drug users in Thailand

Abstract: Background: Behaviour related to injection drug use such as needle and syringe sharing and unsafe sex contribute to the transmission of blood-borne viral infections such as Human Immunodeficiency Virus (HIV), Hepatitis B Virus (HBV), and Hepatitis C Virus (HCV). Therefore, it is recommended that ongoing Injection Drug Users (IDUs) should receive screening for HIV, HBV and HCV at least once every 6 to 12 months. This study aims to estimate prevalence of HIV, HBV and HCV testing uptake among IDUs living in Songk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
2
1
1
Order By: Relevance
“…We suggest that access to treatment in rehabilitation centres should be open to PWID willing to participate and that prevention information on infectious diseases in these centres should be provided. As with other studies conducted in Thailand [29,30,57], we found very low HCV awareness and screening uptake among PWID in Chiang Mai. However, at the time of our study, PWID seemed to have confidence in health centres providing methadone.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…We suggest that access to treatment in rehabilitation centres should be open to PWID willing to participate and that prevention information on infectious diseases in these centres should be provided. As with other studies conducted in Thailand [29,30,57], we found very low HCV awareness and screening uptake among PWID in Chiang Mai. However, at the time of our study, PWID seemed to have confidence in health centres providing methadone.…”
Section: Discussionsupporting
confidence: 87%
“…One study among male PWID in Southern Thailand has evaluated the uptake of HCV testing at 39.5% [29], another among PWID in Bangkok at 33% [31], and yet another among HIV-positive PWID in Bangkok at 52.2% [30]. Compared to our results, these higher rates may be due to more contacts with harm reduction organizations where HCV testing is promoted.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Although attention has been paid to the importance and determinants of HCV treatment uptake among infected drug users , few studies have examined the prevalence of and the factors associated with testing uptake in this population . Importantly no study is known to the authors that has examined how individual PWID characteristics differentially associate with recent (i.e., in the past 12 months) and past or no HCV test uptake.…”
Section: Introductionmentioning
confidence: 99%